Bruxism-induced parotitis: A retrospective case series analysis. Issue 2 (3rd March 2020) - Teymoortash, Afshin; Hoch, Stephan; Weber, Daniel; Wilhelm, Thomas; Günzel, Thomas
ABSTRACT: Objective : A group of patients with recurrent parotitis had clinical symptoms suggesting an obstruction of the glandular duct system, though without any signs of sialoliths or other ductal pathologies. Methods : Clinical and radiological data of five patients with recurrent obstructive parotitis and long-standing definite bruxism were reviewed retrospectively. Ultrasonography, MRI, and sialendoscopy were performed for evaluation of ductal pathologies as the cause of glandular obstruction. Electromyography was used to evaluate the activity of masticatory muscles in all patients. The parotitis was treated with injection of botulinum toxin into the buccinator muscle. Results : Dilatation of the Stensen's duct proximal to the area of the buccinator muscle was shown in radiological examination with no evidence of ductal strictures. Electromyography revealed an abnormal activity of the ipsilateral buccinator muscle. All patients were free of disease after treatment of the buccinator muscle. Discussion : Bruxism should be considered as a possible cause of recurrent parotitis.